Penerapan Keterampilan Dasar Mengajar Mahasiswa PGSD Universitas Triatma Mulya - Sudewiputri, Md Padmarani; Astuti, Ni Md Ignityas Prima; Febryan, Irwan (ANTHOR: Education and Learning Journal, 2023)
This study uses a qualitative method with a descriptive design. This study aims to obtain an as-is picture of how the skills of PGSD students who are carrying out Field Experience Practice at SD Negeri 1 Lelateng. The data obtained from this research is the result of document analysis,observations, and interviews with teachers, students, and PGSD students. This research wasconducted at SD Negeri 1 Lelateng. The type of data used in this study is in the form of narratives,descriptions, explanations, and assessments from informants both orally and in writing which isdescribed in the form of field notes, questionnaires, and documentation. The data source for this research was PGSD students who were carrying out PPL at SD Negeri 1 Lelateng. The informants in this study were PPL supervisors and tutors at SD Negeri 1 Lelateng. The results of this study indicate that explaining skills have been mastered very well. Meanwhile, skills for askingquestions, skills for opening and closing lessons, skills for guiding small group discussions, skillsfor teaching small groups and individuals, skills for managing classes, and skills for providingreinforcement have obtained good results. The skill of carrying out variations obtains quite goodresults.